2014
DOI: 10.17014/ijog.v1i3.198
|View full text |Cite
|
Sign up to set email alerts
|

Eo-Oligocene Oil Shales of the Talawi, Lubuktaruk, and Kiliranjao Areas, West Sumatra: Are they potential source rocks?

Abstract: To anticipate the increasing energy demand, additional data and information covering unconventional fossil fuels such as oil shale must be acquired to promote the usage of alternative energy sources to crude oil. The Talawi and Lubuktaruk regions situated within intra-montane Ombilin Basin, and the Kiliranjao area assumed to be located in a small intra montane Kiliranjao Sub-basin are occupied by Eo-Oligocene sediments of Sangkarewang and Kiliran Formations, respectively. Field activity, geochemical screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…K, Mg and Na account only in minor amount (b1%). The high amount of Ca in the shale confirms that Paleogene source rocks in the most depocenters of the basin are typically calcareous as previously reported by Iqbal et al (2014), Sunardi (2015). The occurrence of carbonates in the lacustrine Kiliran Jao oil shale is interesting and will be discussed elsewhere.…”
Section: Geochemical Compositionsupporting
confidence: 83%
See 1 more Smart Citation
“…K, Mg and Na account only in minor amount (b1%). The high amount of Ca in the shale confirms that Paleogene source rocks in the most depocenters of the basin are typically calcareous as previously reported by Iqbal et al (2014), Sunardi (2015). The occurrence of carbonates in the lacustrine Kiliran Jao oil shale is interesting and will be discussed elsewhere.…”
Section: Geochemical Compositionsupporting
confidence: 83%
“…The general sediment succession of the Kiliran Jao Sub-basin is presented in Fig. 2b based on Iqbal et al (2014), Sunardi (2015) and the references therein. The pregraben paleosol most probably corresponds to the Lower Red Beds Fm.…”
Section: Geology Of the Kiliran Jao Sub-basinmentioning
confidence: 99%
“…The quarry samples belong to the Kiliran Jao/Pematang Formation of the Kiliran Jao Sub-basin (e.g., Iqbal et al, 2014;Sunardi, 2015;Widayat et al, 2016) and the Sumatran highway samples belong to the Sangkarewang Formation of the Ombilin Sub-basin (e.g., Koesoemadinata and Matasak, 1981). We classify samples of the Kiliran Jao Formation based on their lithofacies into mudstone (MDS), massive mudstone (MAS), papery laminated shale (PAP; Widayat et al, 2016), sandy mudstone (SDM), and sandstone (SST).…”
Section: Surface-outcrop Samplesmentioning
confidence: 99%
“…Several researchers, i.e. Carnell et al (1998), Aswan et al (2009), Widayat et al (2013), and Iqbal et al (2014 concluded that the Eocene-Oligocene sediments in Kiliran Jao Subbasin was deposited in lacustrine to brackish environments associated with a coal deposition.…”
Section: Introductionmentioning
confidence: 99%